The congruence and currency of Comenius's understanding of the theory and practice of preschool and family education - Semiz, Marina; Ilić , Marko (Norma, 2023)
The aim of this paper is to consider the currency of Comenius's understandings of preschool and family education, and their congruence with the modern theory and practice of preschool and family education. In this context, a comparative research was conducted, utilizing the method of theoretical analysis, and the technique of content analysis. The comparative analysis implies that many of Comenius's ideas are still relevant, and congruent with contemporary theoretical and empirical knowledge about preschool and family education to a great extent. The conformity of attitudes within the pedagogical system was recorded, despite the fact that Comenius's attitudes regarding children's nature and childhood, goals, importance and content of early childhood education and family environment, as well as the role of parents in that process were presented and developed in unique historical and sociopolitical circumstances. Although the comparative analysis carried out has certain limitations (selective choice of primary and secondary sources of analysis, difficulties in establishing equivalence), this work can be a stimulus for further elaboration of Comenius' essential understandings of preschool and family education in conditions of increasingly complex crises in education and the family.
Keywords: preschool education; family education; early childhood; preschool age; childhood